2020
DOI: 10.18844/gjgc.v10i3.4859
|View full text |Cite
|
Sign up to set email alerts
|

Influence of demographic factors on guidance needs of teacher trainees in Ghana

Abstract: The guidance needs of a particular student or group of students are likely to differ and evolve based on different variables. However, information on the influence of certain demographic variables on the guidance needs of teacher trainees at the Colleges of Education level in Ghana seems to be unavailable. Our purpose in this study was to investigate whether the guidance needs of teacher trainees in the Colleges of Education in Ghana varied based on their sex, age, marital status and the college in which they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…From the findings, it was identified that there were some lack of patronage of the guidance and counselling services that influence the services negatively. This agrees with the findings of recent studies by Appiah, 2013;Nyarko-Sampson, 2013;Sedofia & Kumassah, 2020) that students of colleges of education have seemingly been deprived of guidance and counselling services and their problems are still with them for all these years.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…From the findings, it was identified that there were some lack of patronage of the guidance and counselling services that influence the services negatively. This agrees with the findings of recent studies by Appiah, 2013;Nyarko-Sampson, 2013;Sedofia & Kumassah, 2020) that students of colleges of education have seemingly been deprived of guidance and counselling services and their problems are still with them for all these years.…”
Section: Discussionsupporting
confidence: 92%
“…The aims and objectives of guidance and counselling services as spelt out in the policy statement of the Ghana government were goaloriented and focused on the holistic growth and development of the Ghanaian students. A number of researchers and authors contend that guidance and counselling programmes need to become more closely aligned with state and national standards for schools' counsellors (Lam & Hui, 2010;Aba-Afari, 2011;Nyarko-Sampson, 2013;Awinsong, Dawson, & Gidiglo, 2015, Sedofia, & Kumassah, 2020. Nevertheless, as part of the curriculum and course structure, Colleges of Education are to offer effective guidance and counselling services (Nyarko-Sampson, 2010;Aidoo, 2011;Nyarko-Sampson, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the process of evaluation, a comprehensive evaluation of teachers' teaching ability, knowledge level, and political quality are mainly carried out. When evaluating the teaching of teachers, we should combine our own situation and choose the evaluation methods and evaluation elements reasonably [14].…”
Section: Teaching Evaluationmentioning
confidence: 99%
“…At the international level, the issue of teachers' views on general assessment has been widely studied, but it is worth mentioning that in the Republic of Kazakhstan it is not fully explored in terms of summative assessment within specific in-service training courses. Therefore, it is important to study the attitude of teachers to assessment in professional development courses (Sedofia & Kumassah, 2020;Jahangard, Rahimi, & Norouzizadeh, 2020). Gibbs and Simpson (2004) stated that the system of assessment of learners has a strong impact on the learning process and learning outcomes.…”
Section: Introductionmentioning
confidence: 99%